La gouvernance de l’entreprise dans la tradition rawlsienne : perspectives institutionnaliste et agentielle - Sandrine Blanc (Œconomia)
This article reviews the debates surrounding the critical potential of the Rawlsian conception of justice for corporate governance and how this potential has been exploited over the last twenty years. It highlights two Rawlsian-inspired approaches to corporate governance, one institutionalist and the other centred on the idea of the firm as an agent bearing obligations of justice. In each case, it identifies the elements of continuity and those that are critical of Rawlsian doctrine. These two approaches lead to distinct practical recommendations. The institutionalist approach favours employee participation in governance bodies. The approach that views the firm as an agent bearing obligations of justice favours the integration of external members representing a public reason into a new supervisory board. These options and how they are articulated are at the center of contemporary debates on corporate governance.